Analisis Framing Berita Kasus Tuduhan Pelanggaran UU Informasi dan Transaksi Elektronik (UU ITE) terhadap TikTokers Bima Kritik Lampung di Media Online Detik.com dan Kompas.com - Muhammad Iqbal (Program Studi Ilmu Komunikasi FISIP UM Buton, 2023)
Social media provides freedom of opinion and expression for its users. In Indonesia, the use of social media is regulated in the 2008 ITE Law. This study examines the reporting of one of the ITE Law controversy cases in the form of accusations of hate speech containing SARA against Bima Yudho Saputro who criticized Lampung as